Composites of Heavy Rain Producing Elevated Thunderstorms in the Central United States. (20th June 2017) - McCoy, Laurel P.; Market, Patrick S.; Gravelle, Chad M.; Graves, Charles E.; Fox, Neil I.; Rochette, Scott M.; Kastman, Joshua; Svoma, Bohumil
Abstract : Composite analyses of the atmosphere over the central United States during elevated thunderstorms producing heavy rainfall are presented. Composites were created for five National Weather Service County Warning Areas (CWAs) in the region. Events studied occurred during the warm season (April–September) during 1979–2012. These CWAs encompass the region determined previously to experience the greatest frequency of elevated thunderstorms in the United States. Composited events produced rainfall of >50 mm 24 hr −1 within the selected CWA. Composites were generated for the 0–3 hr period prior to the heaviest rainfall, 6–9 hours prior to it, and 12–15 hours prior to it. This paper focuses on the Pleasant Hill, Missouri (EAX) composites, as all CWA results were similar; also these analyses focus on the period 0–3 hours prior to event occurrence. These findings corroborate the findings of previous authors. What is offered here that is unique is (1) a measure of the interquartile range within the composite mean fields, allowing for discrimination between variable fields that provided a strong reliable signal, from those that may appear strong but possess large variability, and (2) composite soundings of two subclasses of elevated thunderstorms. Also, a null case (one that fits the composite but failed to produce significant rainfall) is also examined for comparison.